Design of 3D Oxide–Metal Hybrid Metamaterial for Tailorable Light–Matter Interactions in Visible and Near‐Infrared Region. Issue 1 (8th November 2020) - Zhang, Di; Lu, Ping; Misra, Shikhar; Wissel, Ashley; He, Zihao; Qi, Zhimin; Gao, Xingyao; Sun, Xing; Liu, Juncheng; Lu, Juanjuan; Zhang, Xinghang; Wang, Haiyan
Abstract: Dielectric–metallic hybrid metamaterials exhibit extraordinary optical properties due to the light–matter interactions at the dielectric–metallic interfaces. The ability in precision control of the light–matter interactions in nanoscale is key to tailor the optical properties of hybrid metamaterials. In this work, a complex 3D framework of multilayered self‐assembled BaTiO3 (BTO)‐Au hybrid thin films is demonstrated with such precision control of the light–matter interaction in nanoscale. Unique "bamboo‐like" Au nanostructures are formed via the bilayer and trilayer stacking of BTO‐Au hybrid layers with interlayers of SrTiO3, CeO2, or MgO. Different film strain states introduced by the three interlayers result in variable diameter and density of Au nanopillars. Both simulated and experimental optical data demonstrate the localized surface plasmon resonance change and hyperbolic dispersion wavelength shift in visible to near‐infrared because of the effective tuning of the Au nanopillar aspect ratio and free electron density. The highly tunable optical properties along with the ferroelectric behavior and thermal robustness of the 3D hybrid film enable it to be a great candidate for multifunctional applications. This study demonstrates a unique 3D approach for precision optical property tuning and combined functionalities in oxide–metal metamaterial systems toward future integrated photonic and electronic devices. Abstract : 3D multilayer BaTiO3 –Au hybrid films with various ultrathin dielectric interlayers have been successfully integrated. Highly tunable optical properties, such as plasmonic resonance and hyperbolic dispersion, are demonstrated within the multilayered structure due to the dimension and density change of the Au nanopillars. The "bamboo‐like" multilayer design enables oxide–metal hybrid films with broader optical tunability towards nanophotonic device applications.